Phase Identification of Low-Voltage Users with Novel Grey Relational Analysis Method. Issue 4 (July 2020) - Zhao, Guowei; Zhao, Rui; Gu, Yuanjie; Chang, Bo; Hu, Changlong; Xue, Yang
Abstract: With the development of smart grid, the extensive use of advanced metering infrastructure (AMI) equipment further improves the lean management level of grid, which makes it possible to accurately analyse the power consumption information of low-voltage users. This paper proposes a novel algorithm for accurately identifying the phase of low voltage users. The algorithm is based on grey relational analysis (GRA). Data collected from independent users and buses are used for comparative analysis by proposed algorithm. In this paper, the algorithm and its experimental results in Hebei Province are introduced in detail. The results show encouraging results that the proposed algorithm can accurately identify the low-voltage users' electricity phase, and the performance of the improved GRA algorithm is better than the traditional GRA. The proposed method also has better effect compared with other methods of phase identification.